Planning and Implementation of Small Hydropower (SHP) Projects - Singal, Sunil K. (Hydro Nepal: Journal of Water, Energy and Environment, 2010)
Small hydropower project is a clean source of power, which India has in abundance. Small hydropower projects are site specific and need careful planning for project formulation and implementation. In this paper an attempt is made to discuss types of small hydropower schemes and present a methodology on planning and implementation of small hydropower projects. Key words: Feasibility; Investigations; Planning; Project Formulation; Small hydropower DOI: 10.3126/hn.v5i0.2480 Hydro Nepal Vol. 5, July 2009 Page:21-25